Cognitive processes in stereotype formation: the role of correct contingency learning for biased group judgments. - Meiser, T; Hewstone, M (2004)
Three studies investigated contingency learning and stereotype formation in a scenario about group membership and behavior with a confounding context factor. The studies tested predictions from theoretical accounts of biased group judgments in terms of simplistic reasoning, parallel distributed memory, and pseudocontingencies. Study 1 revealed a positive correlation between erroneous stereotype formation and learning of the true contingencies with the confounding factor. Study 2 showed that a focus manipulation during encoding moderated the correlation between stereotype formation and contingency learning but not the strength of the erroneous stereotype. Study 3 used a quasiexperimental comparison between participants with biased versus unbiased group judgments and extended the findings of a positive relation between stereotype formation and contingency learning. The results support an explanation of biased group judgments by pseudocontingencies; that is, unwarranted inferences from accurately perceived bivariate correlations in complex environments.